Crossing Design Boundaries : Proceedings of the 3rd Engineering & Product Design Education International Conference, 15-16 September 2005, Edinburgh, UK /: Proceedings of the 3rd Engineering & Product Design Education International Conference, 15-16 September 2005, Edinburgh, UK. (2014) - Unknown
No abstract available